La formazione tra «vite di scarto» e «vita buona» - Rinaldi, Walter (Studi sulla Formazione/Open Journal of Education, 2009)
The postmodern age is marked by human and social complexity. The growth of poverty, the asimmetry between West and East and the globalization of economy asked a critical reflection in particular inside educational theories. The life long learning is one of most important perspective through we can read the contemporary contest.